Preliminary Survey of Graded Diagnosis and Treatment of Rehabilitation Outpatients and Influencing Factors for Downward Referral in Haikou Area - LIN Xiafei; PAN Jingjing; WU Haixia; SUI Yanfang; HUANG Yingyuan; ZENG Ji; SONG Zhenhua; WANG Yulong (康复学报)
ObjectiveTo investigate the awareness of graded diagnosis and treatment model among residents in Haikou City, and analyze the influencing factors of downward referral.MethodsA total of 311 patients treated in the rehabilitation clinic of Haikou Affiliated Hospital of Central South University Xiangya School of Medicine (Haikou People's Hospital) from October to December 2023 were selected as the research subjects by convenience sampling method. A self-designed questionnaire was used to collect the general information of the patients, understand their awareness of the gradede diagnosis and treatment system, their choice of medical treatment, and their experience of downward referral.ResultsAmong the 311 patients, the awareness rate of graded diagnosis and treatment was only 31.83%. In the choice of institutions for emergency medical treatment, 82.32% of patients chose general hospitals, 2.89% chose specialized hospitals, 7.40% chose traditional Chinese medicine hospitals, 5.14% chose health service stations and 7.40% chose primary medical institutions. In the choice of institutions for routine medical treatment, 81.67% of patients chose general hospitals, 2.89% chose specialized hospitals, 9.00% chose traditional Chinese medicine hospitals and 6.43% chose primary medical institutions. Of the 311 patients, only 67 (21.54%) had experiences of downward referral. Univariate analysis showed that educational background, type of medical insurance, annual family income, place of residence and distance to the nearest primary medical institution were the related factors for downward referral of patients (P<0.05). The results of multivariate Logistic regression analysis showed that the main factors affecting the downward referral experience of residents were education background and place of residence. Residents with primary school education had the most downward referral experience, 1.598 times that of those without education (OR=1.598, P=0.037). The downward referral experience of residents who lived in urban rural fringe areas (OR=0.155, P=0.005), town rural fringe areas (OR=0.125, P=0.004), and township centers (OR=0.090, P<0.001) decreased in turn.ConclusionIn Haikou area, the overall awareness of graded diagnosis and treatment among patients is low, and the consultation rate to primary medical institutions is low. It is necessary to strengthen the publicity and education of graded diagnosis and treatment policy, improve patients' awareness of graded diagnosis and treatment system information, guide reasonable medical seeking behavior, and improve the corresponding implementation measures of the graded diagnosis and treatment system to promote its implementation.